2021
DOI: 10.3390/nano11082030
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquids for Development of Heterogeneous Catalysts Based on Nanomaterials for Biocatalysis

Abstract: The development of effective methods of enzyme stabilization is key for the evolution of biocatalytic processes. An interesting approach combines the stabilization process of proteins in ionic liquids and the immobilization of the active phase on the solid support. As a result, stable, active and heterogeneous biocatalysts are obtained. There are several benefits associated with heterogeneous processes, as easy separation of the biocatalyst from the reaction mixture and the possibility of recycling. Accordingl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 99 publications
0
19
0
Order By: Relevance
“…[202][203][204] Compared with catalysts alone, catalysts loaded on SAs not only improved stability but also are easier to facile recovery and reuse. 205,206 For example, Lisboa et al 207 loaded lipase onto SAs. Aer incubation at 40 C for 6 days, free lipase was inactivated, while the activity of lipase loaded on SAs was more than 50%.…”
Section: Other Applicationsmentioning
confidence: 99%
“…[202][203][204] Compared with catalysts alone, catalysts loaded on SAs not only improved stability but also are easier to facile recovery and reuse. 205,206 For example, Lisboa et al 207 loaded lipase onto SAs. Aer incubation at 40 C for 6 days, free lipase was inactivated, while the activity of lipase loaded on SAs was more than 50%.…”
Section: Other Applicationsmentioning
confidence: 99%
“…[12] As part of our continued interest in optimizing the syntheses and applications of carbohydrate-based ionic liquids (CHILs), [13][14][15] a rapidly growing topic in the recent years, [16] we were investigating the use of CHILs in biocatalysis. Ionic liquids are generally well-known in biocatalysis, for example as reaction medium [17] or as support for the immobilized enzymes, [18] amongst other uses. Recent work from Boncel, Chrobok et al…”
Section: Introductionmentioning
confidence: 99%
“…25 To completely utilize the enhanced properties of ILs and reduce their use, ILs as modifiers or bridging molecules for enzyme immobilization is a feasible way. 25 As reported that imidazole-based ILs were covalently grafted onto magnetic composites and the synthesized composites were used as supports for lipase immobilization. The immobilized lipase was used for the production of trans-free plastic and showed good catalytic activity and magnetic response.…”
Section: Introductionmentioning
confidence: 99%